Pharmaceutical Pollution in Aquatic Ecosystems: Impacts and Bioremediation Strategies - Ankita; Sharma, Arvind (Geography, Earth Science and Environment: Research Highlights Vol. 4, 2025)
With the increase in demand for pharmaceuticals globally due to the increasing human population, the pollutants in the aquatic ecosystem are reaching staggering levels. Most of the pharmaceutical contaminants are not effectively removed by conventional wastewater treatment plants (WWTPs). This study explores biomedical strategies as a promising solution for this prominent challenge. Pharmaceutical contaminants such as antibiotics, NSAID (Non-steroidal anti-inflammatory drugs), endocrine disruptors, antidepressants, antihypertensives, steroids, and chemical residues from pharmaceutical industries and pose a great risk to aquatic ecosystems and public health (Growther et al., 2022). Some of its key impacts include disrupting biodiversity, antibiotic resistance, and interference with hormonal systems in aquatic organisms. Promising technologies like bioremediation are potential solutions but their application at an industrial or environmental scale requires further development.